1996
DOI: 10.1021/es9402967
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Interactions between Cr(VI) and Hydrous Concrete Particles

Abstract: Chemical interactions between Cr(VI) and concrete particles in synthetic groundwater solutions were studied. Results indicate that redox, adsorption, and precipitation are the three major reactions occurring at the concrete−water interface. The solution pH plays a significant role in determining the characteristics of chromium reaction behavior with concrete materials. In acidic systems, Cr(VI) species are removed from the solution by reduction reactions. At pH < 4.0, Cr(VI) reacts with aqueous Fe(II) ion, der… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
27
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 26 publications
6
27
0
Order By: Relevance
“…However, CACs were never previously reported as the primary Cr 6+ -containing phases in COPR. Weng et al [19] and Meegoda et al [20] studied COPR obtained from N.J. deposition sites, but were not able to identify Cr 6+ -containing phases by XRPD. Hillier et al [21] investigated COPR deposited in Scotland and reported the following phases as candidates for Cr 6+ speciation: hydrogarnet, hydrocalumite and ettringite.…”
Section: Resultsmentioning
confidence: 99%
“…However, CACs were never previously reported as the primary Cr 6+ -containing phases in COPR. Weng et al [19] and Meegoda et al [20] studied COPR obtained from N.J. deposition sites, but were not able to identify Cr 6+ -containing phases by XRPD. Hillier et al [21] investigated COPR deposited in Scotland and reported the following phases as candidates for Cr 6+ speciation: hydrogarnet, hydrocalumite and ettringite.…”
Section: Resultsmentioning
confidence: 99%
“…Clearly, the original form of Cr(VI) in soil has been converted to less toxic Cr(III) after EK treatment. Under acidic condition, Cr(VI) can be rapidly reduced to Cr(III) by both Fe(II) and/or organic matter [3,32,33]. During the EK remediation, albeit, the soil without contained the available reductive substances, the occurrence of Cr(VI) reduction was showed [13,14].…”
Section: Cr Migration and Removalmentioning
confidence: 99%
“…The concentration values in most of the cases were clearly above the 5 ppm limit, and they even exceeded 40 ppm. Given the great insolubility of Cr(OH) 3 , 24 this behavior indicates speciation of the chromium as Cr(VI). It can also be observed that some of the minimum values of chromium occur in the pH interval between 6.5-7.5, precisely in the interval where the greatest solubilization of zinc and cadmium occurs.…”
Section: Concerning the Complementary Limits Shown Inmentioning
confidence: 99%
“…This is corroborated by the bibliography consulted. 24 Considering these results, it was decided to maintain the pH for the reduction reaction of the Cr(VI) at values greater than but close to 6.…”
Section: Reduction Pretreatment With Fesomentioning
confidence: 99%